Reprogramming rat astrocytes into neurons using small molecules for cell replacement following intracerebral hemorrhage. Issue 3 (September 2021) - Feng, Yangyang; Bai, Shuang; Li, Gaigai; Nie, Hao; Chen, Shiling; Pan, Chao; Zhang, Ping; Tang, Yingxin; Liu, Na; Tang, Zhouping
Astrocytes are promising source cells to replace neurons lost to disease owing to a shared lineage and capacities for dedifferentiation and proliferation under pathological conditions. Reprogramming of astrocytes to neurons has been achieved by transcription factor modulation, but reprogramming in vitro or in vivo using small‐molecule drugs may have several advantages for clinical application. For instance, small molecules can be extensively characterized for efficacy, toxicity, and tumorigenicity in vitro ; induce rapid initiation and subsequent reversal of transdifferentiation upon withdrawal, and obviate the need for exogenous gene transfection. Here we report a new astrocyte–neuron reprogramming strategy using a combination of small molecules (0.5 mM valproic acid, 1 μM RepSox, 3 μM CHIR99021, 2 μM I‐BET151, 10 μM ISX‐9, and 10 μM forskolin). Treatment with this drug combination gradually reduced expression levels of astroglial marker proteins (glial fibrillary acidic protein and S100), transiently enhanced expression of the neuronal progenitor marker doublecortin, and subsequently elevated expression of the mature neuronal marker NeuN in primary astrocyte cultures. These changes were accompanied by transition to a neuron‐like morphological phenotype and expression of multiple neuronal transcription factors. Further, this drug combination induced astrocyte‐to‐neuron transdifferentiation in a culture model of intracerebral hemorrhage (ICH) and upregulated many transdifferentiation‐associated signaling molecules in ICH model rats. In culture, the drug combination also reduced ICH model‐associated oxidative stress, apoptosis, and pro‐inflammatory cytokine production. Neurons derived from small‐molecule reprogramming of astrocytes in adult Sprague–Dawley rats demonstrated long‐term survival and maintenance of neuronal phenotype. This small‐molecule‐induced astrocyte‐to‐neuron transdifferentiation method may be a promising strategy for neuronal replacement therapy.